2014
DOI: 10.1590/s0034-759020140509
|View full text |Cite
|
Sign up to set email alerts
|

Stock Exchange Listing Induces Sophistication of Capital Budgeting

Abstract: This article compares capital budgeting techniques employed in listed and unlisted companies in Brazil. We surveyed the Chief Financial Officers (CFOs) of 398 listed companies and 300 large unlisted companies, and based on 91 respondents, the results suggest that the CFOs of listed companies tend to use less simplistic methods more often, for example: NPV and CAPM, and that CFOs of unlisted companies are less likely to estimate the cost of equity, despite being large companies. These findings indicate that sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Even though the finance literature on small and medium-sized businesses may be relevant, they have not been as widely studied as they should be, given their particular relevance to emerging economies (Hermes et al, 2007;Lazaridis, 2004;Mendes-Da-Silva & Saito, 2014). One of the difficulties most indicated when it comes to carrying out studies in finance that focus on smaller businesses is access to information about these companies.…”
Section: Methodsmentioning
confidence: 99%
“…Even though the finance literature on small and medium-sized businesses may be relevant, they have not been as widely studied as they should be, given their particular relevance to emerging economies (Hermes et al, 2007;Lazaridis, 2004;Mendes-Da-Silva & Saito, 2014). One of the difficulties most indicated when it comes to carrying out studies in finance that focus on smaller businesses is access to information about these companies.…”
Section: Methodsmentioning
confidence: 99%
“…Research in other countries has shown that discounted cash flow (DCF) has become the dominant method in e.g., Canada Jog and Srivastava, 1995;Payne et al, 1999), the UK , and the US (Farragher et al, , 2001Graham and Harvey, 2001;Ryan and Ryan, 2002). Other capital budgeting surveys have been conducted in Sweden, Central and Eastern Europe, Italy, France, Spain, China, the Netherlands, Hong Kong, Indonesia, and more (Brounen et al, 2004;Daunfeldt and Hartwig, 2014;Hermes et al, 2007;Holmén and Pramborg, 2009;Kester et al, 1999;Maquiera et al, 2012;Mendes-Da-Silva and Saito, 2014). Denmark has also been included in such studies.…”
Section: Chapter 4 State-of-the-art Use Of Capital Budgeting Techniqu...mentioning
confidence: 99%